Mesoporous Zr-doped CeO2 nanostructures as superior supercapacitor electrode with significantly enhanced specific capacity and excellent cycling stability. (20th January 2020) - Sun, Mengxuan; Li, Zhijie; Li, Hao; Wu, Zhonglin; Shen, Wenzhong; Fu, Yong Qing
Abstract: Due to its good chemical stability and outstanding redox properties, CeO2 has been regarded as a promising electrode material for supercapacitors, but its specific capacity is quite low which restricts its wide-range applications. To enhance its specific capacity, in this study, specially designed mesoporous Zr-doped CeO2 nanostructures with large surface area, extraordinarily high porosity and abundant oxygen vacancies were fabricated using a hydrothermal method and an assisted calcination process. The synthesized mesoporous CeO2 -Zr-1 nanostructures (with an atomic ratio of Ce:Zr = 10:1) were composed of nanocrystals with an average size of 6.7 nm, and had a large surface area of 81.0 m 2  g −1, and abundant mesopores with a volume of 0.2108 cm 3  g −1 . In 2 M KOH electrolyte, the CeO2 -Zr-1 electrode generated a much larger specific capacity (448.1 C g −1 ) than that of the pristine CeO2 (249.3 C g −1 ) at a current density of 1 A g −1 . An asymmetric supercapacitor of CeO2 -Zr-1//activated carbon produced a high energy storage density of 23.3 Wh kg −1 at 398.5 W kg −1, and an excellent long-term cycling stability with 96.4% capacity retention after 6000 cycles. Graphical abstract: Image 1